Spotlight on tavaborole for the treatment of onychomycosis - Jinna S; Finch J (Dove Medical Press, 2015)
Sphoorthi Jinna, Justin Finch Department of Dermatology, University of Connecticut School of Medicine, Farmington, CT, USA Abstract: Onychomycosis is a fungal nail plate infection that has been increasing in prevalence. A variety of oral and topical anti-fungal agents are currently available but their use is limited by their adverse effect profile, drug–drug interactions, and limited efficacy. Therefore, there is a great need for newer anti-fungal agents. Tavaborole is one of these newer agents and was approved by the US Food and Drug Administration in July 2014 for the topical treatment of mild to moderate toenail onychomycosis. Tavaborole is a novel, boron-based anti-fungal agent with greater nail plate penetration than its predecessors, due to its smaller molecular weight. It has proven through several Phase II and III trials that it can be a safe and effective topical agent for the treatment of mild to moderate toenail onychomycosis without the need for debridement. In this paper, we review the landscape of topical and systemic treatment of onychomycosis, with particular attention to the pharmacokinetics, safety, and efficacy of topical tavaborole. Keywords: tavaborole, boron-based antifungals, oxaboroles, onychomycosis